Surgical Method for the Treatment of Multiplanar Deformities of the Proximal Femur in Children with Aseptic Necrosis of the Femoral Head (Texas Journal of Medical Science, 2022)
The aim of the study was to evaluate the effectiveness of corrective intertrochanteric osteotomies of the femur in multiplanar deformities of the proximal femur after bloodless reduction of congenital hip dislocation in children.